The Role of the National Land Agency in the Complete Systematic Land Registration (PTSL) Program - Halimah, Siti; Widayati, Widayati (Jurnal Konstatering, 2022)
This study aims to analyze: 1) The role of the National Land Agency in the Complete Systematic Land Registration Program (PTSL) 2) Complete Systematic Land Registration Process (PTSL). The approach method used in this research is a sociological juridical approach. The specification of the research used is descriptive analytical research. Types of data using primary data and secondary data obtained through interviews and literature. The data analysis method used in this research is descriptive analysis. The results of the study concluded: 1) The role of the National Land Agency in the Complete Systematic Land Registration Program (PTSL) is to disseminate to the public about PTSL as well as being the implementing party for PTSL which includes PTSL planning activities, determining locations, preparing facilities and infrastructure , collecting physical and juridical data, conducting research on juridical data to prove rights, making announcements of physical and juridical data and validation, namely the issuance of land certificates. The role of the Pangandaran Regency Land Office is an authority that is obtained by attribution, namely from Legislation. 2) The Complete Systematic Land Registration (PTSL) process starts from the planning, location determination, preparation, formation and determination of the PTSL adjudication committee and task force, counseling, physical and juridical data collection, juridical data research, physical and juridical data announcement data as well as validation, bookkeeping of rights until, issuance and delivery of certificates are carried out based on statutory regulations. Keywords: Agencies; Land; Roles.